ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN AKADEMIK (TITIP ABSEN) PADA MAHASISWA S1 FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM UNIVERSITAS ISLAM INDONESIA - Yuni Rafita (Universitas Islam Indonesia, 2013)
Entrusted absent has been done among student, not exception for student in The Faculty of Mathematic and Faculty of Natural Science University Islam Indonesia (FMIPA UII). The Presence of student which prove with absent is important component. FMIPA UII have rule for minimum attendance, about 75%. The attendance determine the student can do the semester exam. Absent is important, in addition to be test requirement, the lecturer use it for component to give a mark. Entrusted absent is form of academic fraud which will effect student’s personality and the impact on their behaviour in workplace later. This Research have aim to know factors that influence academic cheating (Entrusted absent) on student in Faculty of Mathematics and Natural Sciences. Deskriptif crosstabs analysis, and regression logistic analysis are used for data analysis method. After a research, and data analysis was done, factors which influence entrusted absent for students are gender variable, student opinion in assess entrusted absent. Male student and some student who have opinion about entrust absent is fine, have more probabilities to do entrusted absent. This research can be used for base to improve student behaviour in order to make them realized that entrusted absent make bad impact for student behaviour.